2019
DOI: 10.1590/0102-7786344066
|View full text |Cite
|
Sign up to set email alerts
|

Acurácia da Reanálise ERA-Interim do ECMWF e sua Aplicação na Estimativa da Deficiência Hídrica no Estado do Paraná, Brasil

Abstract: Resumo A utilização de dados provenientes de modelos atmosféricos globais é uma alternativa para dados meteorológicos de superfície faltantes e sem séries históricas homogêneas subsidiando avaliações em áreas sem informações meteorológicas de superfície bem como na modelagem do balanço hídrico. Assim, objetivou-se determinar a acurácia da reanálise ERA-Interim do ECMWF e avaliar sua aplicação na estimativa da deficiência hídrica no estado do Paraná, Brasil. Foram utilizados dados meteorológicos decendiais de t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This result corroborates the findings of a great deal of the previous work. This is exemplified in the work undertaken by Aparecido et al (2019), in a study in the state of Paraná, Brazil, using ERA-Interim reanalysis, which also found accuracy higher than 90% for the average air temperature throughout the state. Another example of what is meant by (Martins et al, 2017), in a study in the Iberian Peninsula, observed accuracy of data from reanalysis higher than 80% for the maximum air temperature; however, for the minimum temperature, the accuracy was lower.…”
Section: Discussionmentioning
confidence: 91%
“…This result corroborates the findings of a great deal of the previous work. This is exemplified in the work undertaken by Aparecido et al (2019), in a study in the state of Paraná, Brazil, using ERA-Interim reanalysis, which also found accuracy higher than 90% for the average air temperature throughout the state. Another example of what is meant by (Martins et al, 2017), in a study in the Iberian Peninsula, observed accuracy of data from reanalysis higher than 80% for the maximum air temperature; however, for the minimum temperature, the accuracy was lower.…”
Section: Discussionmentioning
confidence: 91%
“…Mean temperatures in the winter range from 7 to 15 °C19 and 25 to 35 °C in the summer. 44,45 The State of Santa Catarina had the lowest air temperatures for all seasons (Table 2), while the State of Maranhão recorded the highest T_s (26.9 °C), Amapá and Pará had the highest T_a (26.7 °C), Amapá the highest T_w (28.3 °C) and Pará the highest T_s (28.3 °C). The states in the Southeast region had T_s ranging from 22.2 to 24 °C and T_w from 18.1 to 19.1 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Photosynthesis, a vital process for good crop productivity, is optimized at air temperatures between 20 and 36 °C, 43 depending on the plant species. Mean temperatures in the winter range from 7 to 15 °C 19 and 25 to 35 °C in the summer 44,45 …”
Section: Resultsmentioning
confidence: 99%
“…The use of data from global atmospheric models in time series studies is a good strategy when there are flaws in the historical series measured by weather stations, but on the other hand, they add another source of uncertainty on the inferences based on these data. In Brazil, the ERA-Interim model has shown good accuracy (DEE et al, 2011;SANTOS et al, 2017;APARECIDO et al, 2019).…”
Section: Discussionmentioning
confidence: 99%